2017
DOI: 10.1002/jms.3979
|View full text |Cite
|
Sign up to set email alerts
|

Fragmentation patterns of 4(5)‐nitroimidazole and 1‐methyl‐5‐nitroimidazole—The effect of the methylation

Abstract: We present here the photofragmentation patterns of doubly ionized 4(5)-nitroimidazole and 1-methyl-5-nitroimidazole. The doubly ionized state was created by core ionizing the C 1s orbitals of the samples, rapidly followed by Auger decay. Due to the recent development of nitroimidazole-based radiosensitizing drugs, core ionization was selected as it represents the very same processes taking place under the irradiation with medical X-rays. In addition to the fragmentation patterns of the sample, we study the eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…However, such an estimate based on the present data is unreliable, because it would be affected by the kinetic energy distribution of the involved fragments, which in turn affects the detection efficiency. photoioni-photoion coincidence (PEPIPICO) experiments (Itälä et al, 2017) reported that the dominant contribution in the fragmentation of doubly/multiply charged 4(5)NIM ions just above the C K-edge corresponds to the release of NO + , while NO2+ is either hardly produced or has a large probability to fragment, consistent with our observations.…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…However, such an estimate based on the present data is unreliable, because it would be affected by the kinetic energy distribution of the involved fragments, which in turn affects the detection efficiency. photoioni-photoion coincidence (PEPIPICO) experiments (Itälä et al, 2017) reported that the dominant contribution in the fragmentation of doubly/multiply charged 4(5)NIM ions just above the C K-edge corresponds to the release of NO + , while NO2+ is either hardly produced or has a large probability to fragment, consistent with our observations.…”
Section: Resultssupporting
confidence: 90%
“…Passing through core excitations and ionizations the fragmentation mechanisms could be different from the ones identified in the valence region, mainly due to the possibility for multiply-charged ion formations. However, the PEPIPICO experiments of (Itälä et al, 2017) in 4(5)NIM at 317 eV photon energy (i.e., still well below the N K edge) do not display any significant signal for ion pairs including m/z fragments heavier than 46. Therefore, we deduced that double ionization events are not the major channels for the production of heavier fragments in 2NIM too.…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…Although the detailed mechanisms by which radiosensitisation operates are still unknown, it is believed that radiosensitisers are chemical compounds subject to redox reactions inside the hypoxic cells [4], and in case of nitroimidazoles, the ring facilitates reduction through reactive anion radicals' formation [5][6][7]. Nitroimidazole radiosensitisers have been thoroughly investigated by experimental methods on low-energy electron interactions [8][9][10][11][12] and together with nimorazole probed by electrospray ionization mass spectrometry [13][14][15]. While associative electron attachment may contribute to NIMO's radiosensitising effect, within the biological environment, electron transfer processes (redox reactions) may prevail and so these may seem more appropriate to describe the underlying molecular mechanisms of such chemical compounds and their role as radiosensitisers.…”
Section: Introductionmentioning
confidence: 99%
“…Decomposition products upon photon excitation were reported in [31] with nitric oxide (NO) and nitrogen dioxide (NO 2 ) as the main fragments. A recent photofragmentation study of doubly charged, core excited 4(5)-nitromindazole (4(5)-NI) showed that methylation at the N1 position (see Scheme 1) suppresses efficiently the NO and NO + production [32]. The first mass spectra of electrosprayed nitroimidazolic compounds, like nimorazole, were recorded by Feketeová et al [33, 34].…”
Section: Introductionmentioning
confidence: 99%